#TITLE_ALTERNATIVE# - BAEHAQI FALAH (NIM 15105051); Pembimbing: Dr. Ir. Eka Djunarsjah, MT., dan Dr. Ir. Andri Hern, ISMAIL
Ocean space utilization activities that resulted in increased complexity increasing interest in marine activities. Complexity is related to the utilization of marine space is three-dimensional (surface, column and seabed). It is necessary for a marine spatial planning to create a marine cadastre can represent the nature of the utilization of ocean space that is by forming a three-dimensional (3D) marine cadastre. To realize the 3D marine cadastre must be examined on technical aspects of 3D marine cadastre so that the utilization of ocean space are guaranteed both legal certainty and physical data at sea. Study of technical aspects of 3D marine cadastre concept started with library research and marine cadastre survey and mapping of the sea, then be studied an engineering aspects of marine cadastre object identification based on 3D marine space utilization. The next stage is implementing marine cadastre technical aspects of each object so as to produce 3D visualization of each object marine cadastre. The results of this study can be seen that the technical aspects of marine cadastre can be applied to each object cadastre marine thereby creating 3D marine cadastre. In addition, 3D visualization objects can be seen marine cadastre in order to show 3D objects based on the utilization of marine cadastre.